PT EMT – Portuguese Emergency Medical Team Type 1 Relief Mission in Mozambique. Issue 5 (2nd October 2021) - Ladeira, Luis M.; Cardoso, Ivo; Ribeiro, Hélder; Lourenço, João; Ramos, Raquel; Barros, Filipa; Rato, Fátima
Abstract: Introduction: The tropical cyclone Idai hit Mozambique in the city of Beira on March 15, 2019. During the following days, the Portuguese Emergency Medical Team (PT EMT) and its infrastructure deployed to Mozambique with the mission of helping local people and collaborating with the authorities. Methods: Data analyzed were collected in the period of the deployment, from April 1-April 30, 2019. All patients admitted to PT EMT were registered through the Clinical Record of PT EMT. Results: In total, 1, 662 patients were admitted to PT EMT during the 30-day mission. The five most prevalent diagnoses were: 61.49% classified with "code 29" (which corresponds to "other unspecified diagnoses"), 9.15% of cases of skin disease, 8.90% of minor injuries, 6.74% of acute respiratory infection, and 3.19% of obstetric/genecology complications. Discussion and Challenges: An important challenge identified was the need for a robust and effective network for transporting patients, allowing transfers between EMTs, enabling a true network response in the provision of care to disaster victims. Conclusions: The benefit of the deployment of PT EMT in Mozambique after Cyclone Idai was in line with the EMT initiative standards, allowing a direct delivery of care to the affected Mozambican population and support to the local health authorities.